Greenhouse Gases Emissions from Wastewater Treatment Plants: Minimization, Treatment, and Prevention - J. L. Campos; D. Valenzuela-Heredia; A. Pedrouso; A. Val del Río; M. Belmonte; A. Mosquera-Corral (Journal of Chemistry)
The operation of wastewater treatment plants results in direct emissions, from the biological processes, of greenhouse gases (GHG) such as carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O), as well as indirect emissions resulting from energy generation. In this study, three possible ways to reduce these emissions are discussed and analyzed: (1) minimization through the change of operational conditions, (2) treatment of the gaseous streams, and (3) prevention by applying new configurations and processes to remove both organic matter and pollutants. In current WWTPs, to modify the operational conditions of existing units reveals itself as possibly the most economical way to decrease N2O and CO2 emissions without deterioration of effluent quality. Nowadays the treatment of the gaseous streams containing the GHG seems to be a not suitable option due to the high capital costs of systems involved to capture and clean them. The change of WWTP configuration by using microalgae or partial nitritation-Anammox processes to remove ammonia from wastewater, instead of conventional nitrification-denitrification processes, can significantly reduce the GHG emissions and the energy consumed. However, the area required in the case of microalgae systems and the current lack of information about stability of partial nitritation-Anammox processes operating in the main stream of the WWTP are factors to be considered.